The Erasmus undergraduate exchange programme: a highly qualified success story? - Cairns, D. (Children's Geographies, 2017)
Erasmus is regarded as a European success story: an example of cross-border cooperation and an opportunity for students to improve their inter-cultural skills and work capacities. This article takes an in-depth look at this success, examining recent trends in Erasmus mobility. Analysis shows that while certain countries have greater numbers of students outgoing than incoming, the converse situation is found in countries such as Portugal. To explain this imbalance, evidence is drawn from a study of Erasmus in Portugal conducted during 2016. While the popularity of the country as a destination is related to low cost of living, friendliness and educational quality, interviews with managers of the Erasmus programme reveal other factors that limit the participation of local students. This includes the low level of Erasmus scholarships for undergraduates from families affected by the economic crisis, with exchange students also increasingly viewed as tourists and consumers as well as learners.